Bright Fluorescence and Host–Guest Sensing with a Nanoscale M4L6 Tetrahedron Accessed by Self‐Assembly of Zinc–Imine Chelate Vertices and Perylene Bisimide Edges1. (29th April 2015) - Frischmann, Peter D.; Kunz, Valentin; Würthner, Frank
Abstract A highly luminescent Zn4L6 tetrahedron is reported with 3.8 nm perylene bisimide edges and hexadentate ZnII–imine chelate vertices. Replacing FeII and monoamines commonly utilized in subcomponent self‐assembly with ZnII and tris(2‐aminoethyl)amine provides access to a metallosupramolecular host with the rare combination of structural integrity at concentrations <10−7 mol L−1 and an exceptionally high fluorescence quantum yield of Φem=0.67. Encapsulation of multiple perylene or coronene guest molecules is accompanied by strong luminescence quenching. We anticipate this self‐assembly strategy may be generalized to improve access to brightly fluorescent coordination cages tailored for host–guest light‐harvesting, photocatalysis, and sensing.